Transcatheter Embolization in the Management of Epistaxis - Dubel, Gregory J. (Thieme Medical Publishers, 2013)
A majority of the population will experience epistaxis at some time in their life. Most cases will be from an anterior source and can be treated with pressure, anterior nasal packing, or cautery. Intractable epistaxis is generally posterior in origin and may require endoscopic cautery, posterior packing, surgical ligation, or embolization. Embolization has been used to treat epistaxis for more than 30 years and success can be achieved in approximately 90% of patients, with major complications occurring in approximately 2%. These excellent results require thorough knowledge of the regional anatomy, familiarity with the equipment and various agents used to achieve this type of embolization, as well as attention to detail and meticulous technique. There remains debate on several aspects of embolization, including the agent of choice, preferred size of the embolic, and the number of vessels to embolize. Advances in endoscopic surgery have evolved to the point that similar success rates for embolization and modern surgical techniques in treating epistaxis may be expected. This detailed review of pertinent vascular anatomy, embolization technique, and surgical alternatives should allow practitioners to formulate treatment algorithms that result in optimal outcomes at their institutions.